An RNase III–processed sRNA coordinates sialic acid metabolism of Salmonella enterica during gut colonization - Ziying Chen; Yaomei Yang; Xiaomin Chen; Cheng Bei; Qian Gao; Yanjie Chao; Chuan Wang (Proceedings of the National Academy of Sciences, 2025)
Sialic acids derived from colonic mucin glycans are crucial nutrients for enteric bacterial pathogens like Salmonella . The uptake and utilization of sialic acid in Salmonella depend on coordinated regulons, each activated by specific metabolites at the transcriptional level. However, the mechanisms enabling crosstalk among these regulatory circuits to synchronize gene expression remain poorly understood. Here, we identify ManS, a small noncoding RNA derived from the 3’ UTR of STM1128 mRNA transcribed from a Salmonella enterica –specific genetic locus, as an important posttranscriptional regulator coordinating sialic acid metabolism regulons. ManS is primarily processed by RNase III and, along with its parental transcripts, is specifically activated by N-acetylmannosamine (ManNAc), the initial degradation product of sialic acid. We found that the imperfect stem-loop structure at the 5’ end of ManS allows RNase III to cleave in a noncanonical manner, generating two functional types of ManS with the assistance of RNase E and other RNases: short isoforms with a single seed region that regulate the uptake of N-acetylglucosamine, an essential intermediate in sialic acid metabolism; and long isoforms with an additional seed region that regulate multiple genes involved in central and secondary metabolism. This sophisticated regulation by ManS significantly impacts ManNAc metabolism and S. enterica ’s competitive behavior during infection. Our findings highlight the role of sRNA in coordinating transcriptional circuits and advance our understanding of RNase III-mediated processing of 3’ UTR-derived sRNAs, underscoring the important role of ManNAc in Salmonella adaptation within host environments.